2022
DOI: 10.1002/ctm2.581
|View full text |Cite
|
Sign up to set email alerts
|

Subversion of infiltrating prostate macrophages to a mixed immunosuppressive tumor‐associated macrophage phenotype

Abstract: Tumor‐associated macrophages (TAMs) support tumor progression within the tumor microenvironment (TME). Many questions remain as to the origin, development, and function of TAMs within the prostate TME. Evaluation of TAMs in prostate cancer (PCa) patients identified the immunosuppressive TAM marker CD163 in adjacent normal epithelium as an independent predictor of metastases or PCa death. Flow cytometry analyses identified prostate TAMs as frequently expressing both proinflammatory M1 (CCR7+) and immunosuppress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Furthermore, researchers observed that when PCa cells were present, M1 phenotype could not be fully restored even with M1-like cytokine stimulation, usually accompanied by diminished cytotoxicity. This finding implies that attempts to repolarize prostate TAMs will be sufficiently effective with concomitantly destroying adjacent tumor cells [ 183 ].…”
Section: Promising Strategies For Pca Treatment Via Targeting Tamsmentioning
confidence: 99%
“…Furthermore, researchers observed that when PCa cells were present, M1 phenotype could not be fully restored even with M1-like cytokine stimulation, usually accompanied by diminished cytotoxicity. This finding implies that attempts to repolarize prostate TAMs will be sufficiently effective with concomitantly destroying adjacent tumor cells [ 183 ].…”
Section: Promising Strategies For Pca Treatment Via Targeting Tamsmentioning
confidence: 99%
“…In addition, we were able to find supporting evidences for the role of the some cell types in the specific cancer types listed in the Fig. 4b [64][65][66][67][68].…”
Section: Global Interpretationmentioning
confidence: 82%
“…5d. Prostate cancer cells decrease the expression of CCR7 in M1 macrophages and increase the expression of M2 markers, which switches inflammatory M1 macrophages to immunosuppressive M2 macrophages [68]. Additionally, CRC tumors are highly infiltrated by effector CD8 T cells, which have lower CCR7 expression than naive and central memory.…”
Section: Local Interpretationmentioning
confidence: 99%
“…For instance, M2 macrophages consume more glutamine intracellularly than M1 macrophages, and glutamine also promotes macrophage polarization to M2 type by modifying the correspondent gene expression [ 19 ]. Additionally, PCa cells can alter the phenotype of recruited macrophages by releasing chemokines to polarize them toward a pro-tumor macrophage mixed state [ 41 ]. Notably, in the current study, we found a significantly higher infiltration of M2 type macrophages and Tregs cells in the high-risk group.…”
Section: Discussionmentioning
confidence: 99%